2022
DOI: 10.1111/vco.12818
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA and transfer RNA‐derived small fragments in exosomes are potential biomarkers for canine oral melanoma

Abstract: Novel small non-coding RNAs (sRNAs) represent an emerging line of research in both human and canine oncology, due to their diverse regulatory and functional roles. Novel sRNAs are regarded as distinct from microRNAs, although both are part of the exosomal cargo. Recently, we reported on exosomal miRNAs as biomarkers for canine melanoma; however, it is unknown if novel sRNAs hold similar potential. Accordingly, we aimed to identify and validate novel sRNAs as potential biomarkers of canine oral melanoma, as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The study identified 55 exosomal lncRNAs that were differentially expressed and lncRNAs ENSCAFT00000069599.1 and EN-SCAFT00000090032.1 verified significantly high expression levels in canine oral melanoma patients [35]. A particularly interesting finding is that lncRNA ENSCAFT00000069599.1 demonstrated the highest diagnostic efficacy, as determined by receiver operating characteristic (ROC) curve analysis of sensitivity and specificity [35]. This suggests that lncRNA ENSCAFT00000069599.1 has the potential to be a valuable diagnostic biomarker for canine oral melanoma.…”
Section: The Molecular Function and Clinical Use Of Lncrna As Canine ...mentioning
confidence: 88%
See 1 more Smart Citation
“…The study identified 55 exosomal lncRNAs that were differentially expressed and lncRNAs ENSCAFT00000069599.1 and EN-SCAFT00000090032.1 verified significantly high expression levels in canine oral melanoma patients [35]. A particularly interesting finding is that lncRNA ENSCAFT00000069599.1 demonstrated the highest diagnostic efficacy, as determined by receiver operating characteristic (ROC) curve analysis of sensitivity and specificity [35]. This suggests that lncRNA ENSCAFT00000069599.1 has the potential to be a valuable diagnostic biomarker for canine oral melanoma.…”
Section: The Molecular Function and Clinical Use Of Lncrna As Canine ...mentioning
confidence: 88%
“…In another study, the analysis focused on novel small non-coding RNAs found in exosomes of two melanoma cell lines (KMeC and LMeC). The study identified 55 exosomal lncRNAs that were differentially expressed and lncRNAs ENSCAFT00000069599.1 and EN-SCAFT00000090032.1 verified significantly high expression levels in canine oral melanoma patients [35]. A particularly interesting finding is that lncRNA ENSCAFT00000069599.1 demonstrated the highest diagnostic efficacy, as determined by receiver operating characteristic (ROC) curve analysis of sensitivity and specificity [35].…”
Section: The Molecular Function and Clinical Use Of Lncrna As Canine ...mentioning
confidence: 91%
“…Small nuclear RNAs (snRNAs) [ 106 ], small nucleolar RNAs (snoRNAs) [ 107 ], and PIWI-interacting RNAs (piRNAs) [ 108 ], are additional ncRNAs that can be discovered in exosomes. In the RNA processing, modification, and genome stability processes, these ncRNA molecules play unique roles [ 107 , 108 ].…”
Section: Components Of Exosomementioning
confidence: 99%
“…Y RNA was selected based on a previously published NGS dataset (SRA: PRJNA716131) for canine mammary gland tumors [36]. The qRT-PCR protocol was described previously [45][46][47]. Briefly, 2 ng (for tissues and cell lines) or 1.25 µL (for plasma and plasma EVs) of total RNA were reverse transcribed to cDNA using the TaqMan MicroRNA Reverse Transcription Kit (Thermo Fisher Scientific) with a T100 thermal cycler, following the manufacturer's protocol.…”
Section: Ncrnas Selection and Qrt-pcrmentioning
confidence: 99%